‘Pathological’ Religiosity Phenomenon as Manifestation of Individual's Deviant Behavior: Religious Hatred or Discord Motive in Commission of Crimes in the Religious Denomination Sphere - Юрчишин, Василь Миколайович; Юрчишин В. М.; Юрчишин, Василий Николаевич; Yurchyshyn, Vasyl M.; Леоненко, Тетяна Євгенівна; Леоненко, Т. Є.; Леоненко, Татьяна Евгеньевна; Leonenko, Tetiana Ye.; Леоненко, Максим Іванович; Леоненко, М. І.; Леоненко, Максим Иванович; Leonenko, Maksym I.; et al. (ASERS Publishing, 2019)
The need to ensure equal rights for all people, regardless of religion, is enshrined in international law and necessitates a comprehensive study of hate crimes to prevent them more effectively. This explains the relevance of this study. The authors consider the phenomenon of crime on a religious ground as a criminal law and as a social and legal phenomenon. The article aims to investigate the phenomenon of ‘pathological’ religiosity as one of the manifestations of deviant behavior of the individual. The authors analyzed the peculiarities of the formation of the motive of religious hatred or hostility in the commission of a crime in the field of religion. The psychological and social factors that influence the formation of such a motive were identified, which allowed to identify the psychological determinants of the structure of the person of the offender who committed a crime on the grounds of religious hatred or hostility.

Необхідність забезпечення рівних прав для всіх людей, незалежно від релігії, закріплене в міжнародному праві і вимагає всебічного вивчення злочинів на ґрунті ненависті для ефективнішого запобігання їм. Це пояснює актуальність цього дослідження. Автори розглядають феномен злочинності на релігійному ґрунті як кримінально-правове та як соціально-правове явище. Метою статті є дослідження феномену «патологічної» релігійності як одного з проявів девіантної поведінки особистості. Авторами проаналізовано особливості формування мотиву релігійної ненависті чи ворожнечі при вчиненні злочину у сфері релігії. Визначено психологічні та соціальні фактори, що впливають на формування такого мотиву, що дозволило виявити психологічні детермінанти структури особи злочинця, який вчинив злочин на ґрунті релігійної ненависті чи ворожості.
Leonenko T. Y. ﹸPathologicalﹸ Religiosity Phenomenon as Manifestation of Individual's Deviant Behavior: Religious Hatred or Discord Motive in Commission of Crimes in the Religious Denomination Sphere / T. Y. Leonenko, M. I. Leonenko, O. Y. Shyian, V. M. Yurchyshyn, O. O. Shkuta // Journal of Advanced Research in Law and Economics. - Vol. 10. – Iss. 1. - ASERS Publishing, 2019. – P. 295-306.
Keywords: deviation; hate crimes; delinquent behavior; addictive behavior; motive crime; motivation; crime; девіація; злочини на ґрунті ненависті; злочинна поведінка; залежна поведінка; мотивований злочин; мотивація; злочин; Research Subject Categories::LAW/JURISPRUDENCE